Nations of nothing but poetry modernism, transnationalism, and synthetic vernacular writing - Hart, Matthew, Ph.D (Modernist literature & culture., 2010)
What happens when poets combine vernacular language with the spirit of modernity? Can a poem be cosmopolitanism and vernacular at the same time? This book answers these questions through case studies of Scottish, English, and 'Black Atlantic' poetries from the landmark modernist year of 1922 through the mid 1970s.